Work study in building operations / Kamal Basha Mohd. Haniffa - Mohd. Haniffa, Kamal Basha (1982)
Time Standards for operations or jobs are essential for construction scheduling, wage incentives, cost control and budgeting, comparison of work methods, etc. Direct Time Study, which is the conventional stopwatch technique was used in this project. It requires the job to be timed to be broken down into its constituent elements which are each timed for a sufficient number of occasions. Since the objective of the project was to determine the time required by a qualified worker using a given method at a defined level of performance, it was necessary, whilst timing, to assess the rate of the operator's performance so that the observed time can be converted to Standard time. The addition of allowances was necessary in order to provide time to compensate for contingencies, delays etc.